2016
DOI: 10.15195/v3.a1
|View full text |Cite
|
Sign up to set email alerts
|

Unequal Hard Times: The Influence of the Great Recession on Gender Bias in Entrepreneurial Financing

Abstract: Prior work finds mixed evidence of gender bias in lenders' willingness to approve loans to entrepreneurs during normal macroeconomic conditions. However, various theories predict that gender bias is more likely to manifest when there is greater uncertainty or when decision-makers' choices are under greater scrutiny from others. Such conditions characterized the lending market in the recent economic downturn. This article draws on an analysis of panel data from the Kauffman Firm Survey to investigate how the Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 64 publications
0
37
0
Order By: Relevance
“…The standard deviation of 1.058, though, showed that respondents' opinions were divided on this issue. Thébaud and Sharkey [45] remark that being part of a network helps women entrepreneurs to conduct their business, especially with men entrepreneurs, which enhances the prospects for business growth.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The standard deviation of 1.058, though, showed that respondents' opinions were divided on this issue. Thébaud and Sharkey [45] remark that being part of a network helps women entrepreneurs to conduct their business, especially with men entrepreneurs, which enhances the prospects for business growth.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…These challenges associated with becoming an entrepreneur are particularly acute for women, who face systematic obstacles when identifying opportunities and accumulating resources required to launch and operate a startup (e.g., Hout and Rosen, ; Keister and Moller, ; Kim et al, ). Indeed, entrepreneurial outcomes show stark disparities across gender lines, including the act of starting and running a new venture (Kacperczyk and Guzman, 2019; Thébaud, , ; Thébaud and Sharkey, ). For example, female‐founded ventures appear severely underrepresented amongst new startups, and gender disparities are stronger among new firms with a high‐growth orientation.…”
Section: Theorymentioning
confidence: 99%
“…Accordingly, women are considered less qualified and less competent entrepreneurs (Bigelow et al, ; Brooks et al, ; Thébaud, ), and such inferences about their “fitness” with entrepreneurial domains tend to reduce investors' willingness to fund female‐founded ventures (Blanchflower et al, ). For example, the odds of receiving credit from suppliers (Freeland and Keister, ), banks (Thébaud and Sharkey, ), or venture capitalists (Brush et al, ; Guzman and Kacperczyk, ) have been found to be significantly lower for women than for observationally equivalent men. And these disparities tend to persist even when differences in creditworthiness or other observables, including human capital, industry, and credit histories, are controlled for (Blanchflower et al, ; Hout and Rosen, ), or in experimental conditions, wherein gender is randomly assigned (Thébaud, ).…”
Section: Theorymentioning
confidence: 99%
“…The widespread use of cognitive shortcuts in the form of gender stereotyping under high levels of uncertainty and risk explains much of the gender gap in venture finance (Thébaud and Sharkey, 2015). On the one hand, this gender dichotomy that associates men and masculinity with competence in high growth, profitcentric entrepreneurship might be believed to provide women with a greater chance of succeeding in the field of social entrepreneurship.…”
Section: Liberal Feminist Interventionsmentioning
confidence: 99%